Latent Profiles and Influencing Factors of Posttraumatic Stress Symptoms Among Adults During the COVID-19 Pandemic - Wenjie Duan; Qiujie Guan; Qiuping Jin (Frontiers Media S.A., 2021)
The COVID-19 pandemic severely affected public health and the prevalence of posttraumatic stress symptoms among adults in Hubei Province, China. In this study, a total of 2,930 (662 males and 2,268 females) adults answered a questionnaire obtaining information on their demographics, posttraumatic stress symptoms (i.e., intrusion and avoidance), social media exposure, social media involvement, and self-efficacy. Results of the latent profile analysis identified four latent profiles of posttraumatic stress symptoms, which are, no symptoms, high intrusion-low avoidance, moderate symptoms, and high symptoms. The multinomial logistic regression analyses revealed the contributors to the posttraumatic stress symptoms subgroups. Adults with high social media involvement were classified into the high intrusion-low avoidance group, whereas adults with low self-efficacy were included in the moderate symptoms group. Meanwhile, adults with high social media involvement and low self-efficacy were included in the high symptoms group. Interventions may focus on decreasing social media involvement for the adults in the high Intrusion-low avoidance group, improving self-efficacy for the adults in the moderate symptoms group, and reducing social media involvement and improving self-efficacy for the adults in the high symptoms group.